Exploring Plausible Effects of GST on Goods and Services Sectors in Western India - Sharma, Priyanshu; Kumar, Mithilesh (Indian Journal of Finance, 2017)
The much hailed as well as debated landmark legislation of GST has the central objective to provide a uniform taxation system across the country. The implementation of GST will for sure bring about a change in the economy and will have a range of direct or indirect impacts on various financial organizations, consumers, markets, and national GDP. For any major change in gross products and services taxation pattern, any state needs to achieve reasonably high level of effectiveness for durable and sustainable development. To find the people’s perception on possible effects or impacts of GST implementation in India, the present study investigated the responses of the respondents over some of the areas like imports, exports, employment generation, and profit. A total of 308 respondents were surveyed using standardized questionnaires in the three Western states of India - Rajasthan, Gujarat, and Maharashtra. The results proved that whereas GST implementation mostly showed a positive impact in different categories, respondents stayed neutral for some of the concerns and for some other areas, GST may not bring desirable changes.